A sociotheological interpretation of Genesis 50:25 in a Zimbabwean context - Mwandayi, Canisius (HTS teologiese studies, 2024)
Migration to foreign lands is as old as the biblical stories of Abraham leaving his native land, Ur of the Chaldeans to go to a land that God was to show him. Concomitant with migration, however, is the possibility of death in the new habitat and oftentimes important decisions are made on how to fund the funerals. In the case of Zimbabwean diasporas, this has seen the rise in popularity of funeral insurance companies such as Diaspora Insurance and the GoFundMe initiatives. While the issue of funding funerals appears to be the primary thing that people are seized with when a funeral strikes, the most salient aspects would be issues of religion and culture. This article endeavours to show how, despite the challenging economic environment, the costly repatriation of dead relatives can best be appreciated through a sociotheological interpretation of Genesis 50:25. In other words, Genesis 50:25 can be used as a mirror to understand the value people place on issues of religion and culture. It is thus my argument that the religious background of the actors as well as their socio-cultural setting are critical in making important decisions regarding the place of interment as well as influencing the funding logistics to take the corpse to the desired resting place.Contribution: As the death toll continues to rise of diasporas who would have gone offshore in search of a reprieve from the economic challenges that have become almost an indelible mark of Zimbabwe, issues around the values of traditional religion and culture continue to come to the fore. This research adds a voice to the ongoing religious and political dialogue in Zimbabwe in so far as it seeks to explain and understand the underlying reasons behind the costly repatriation of deceased relatives through a sociotheological reading of Genesis 50:25.